Assessing the Perceived Impact of Digital Transformation on the Efficiency of Sales Growth in Nepal - Subedi, Khem Raj; Bhatt, Shankar Datt (NPRC Journal of Multidisciplinary Research, 2025)
Digital transformation (DT) involves a broad range of advancements in information and communication technology aimed at optimizing limited resources and driving competitive advantage in the business world. The aim of the paper is to assess the perceived impact of DT on the efficiency of sales growth among small and medium scale enterprises (SMEs) in Nepal. Technology–Organization–Environment (TOE) framework was adopted to fulfil the aim of the research ensuring theoretical relevance and justification. This study is based on the primary data collected from study site during January to April 2025 using purposive sampling within selected strata to fulfil research objective. The analysis involved cross-sectional survey data from 384 SMEs of Kailali and Kanchanpur District of Nepal, and a regression model was estimated to calibrate efficiency in sales growth as the dependent variable. The estimated regression results show that the level of digitization, firm size, adoption of digital payments, age of firm, and cost efficiency all have positive and statistically significant impacts on sales growth efficiency. Moreover, cost efficiency exhibited the largest effect (0.412, p < 0.01), highlighting the importance of cost management in driving revenue growth. Similarly, adoption of digital payments (0.160, p < 0.05) and level of digitization (0.235, p < 0.01) demonstrated significant contributions, reflecting how technology adoption enhances customer experience and operational capabilities. However, SMEs face notable barriers to DT, including poor internet access and high cost, limited technical expertise, and high costs of digital tools. The findings suggest that DT enhances sales performance, its benefits depend on firm-specific resources, readiness, and infrastructure availability. The study provides empirical evidence that supports policy efforts aimed at improving digital infrastructure, lowering adoption costs, and enhancing digital skills and aligns with Sustainable Development Goal 9 (SDG9). Therefore, strengthening these areas could accelerate sales growth efficiency and competitiveness of Nepalese SMEs in an increasingly digital economy.